EFEKTIVITAS LEMBAGA ISLAMIC BROADCASTING AND COMMUNICATION TALENT DEVELOPMENT (I-BRAND) SEBAGAI MEDIA AKTUALISASI MAHASISWA JURUSAN KOMUNIKASI DAN PENYIARAN ISLAM (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
The purpose of this study was to find out the activities of the Islamic Broadcasting and Communication Talent Development (I-brand) Institute in carrying out activities and to find out the effectiveness of the activities of the Islamic Broadcasting and Communication Talent Development (I-brand) Institute as a medium for student actualization of the Islamic Communication and Broadcasting Department. The research method used is qualitative research, namely research that produces data in the form of words or actions both orally and in writing. The source of the data in this study is field data obtained directly from informants without intermediaries. In this study using a scientific approach, namely communication. For the method of data collection is done by observation (observation), interviews, and documentation. Then for the data analysis technique used is the inductive analysis technique. The results of the study show that the activities of the I-brand Institution in carrying out activities are by forming a work program that cannot be separated from the Tripotency of Students of the Islamic Communication and Broadcasting Department such as Broadcasting, Public Speaking and Writing. Then carry out several stages in carrying out activities, namely planning, organizing, directing as when planning activities, namely communicating with the head of the Department and I-brand seniors, then organizing, namely forming several fields that will be responsible for the activities to be carried out, then providing direction so that activities run effectively and in accordance with the initial plan. The effectiveness of the activities of the I-brand Institute can be measured by several conditions, namely economics, achievement of goals and satisfaction in the activity, the training activities carried out by I-brand have been effective because the activities carried out are quite economical and achieve the goals according to what they want and feel satisfied after participating this activity because after participating in the activity they can hone their skills in the fields of Broadcasting, Public Speaking and Writing, and gain useful knowledge that they have not gotten before. The implications of the research based on the results obtained are for the Institute (I-brand) to continue to develop the Tripotency of Islamic Communication and Broadcasting Students in the fields of Broadcasting, Public Speaking and Writing. And to students of the Department of Communication and Islamic Broadcasting at UIN Alauddin Makassar, that joining the Institute (I-brand) can provide added value and also become a place to explore and develop your potential. Keywords: activities, effectiveness, actualization